1‐Adamantanethiol as a versatile nanografting tool. Issue 1 (5th November 2014) - Drexler, Chad I.; Causey, Corey P.; Mullen, Thomas J.
Summary Strategies to regulate the self‐assembly of adsorbates to create surface structures with molecular‐scale features and organization are of broad interest to nanoscience, biochemistry, and engineering. One approach utilizes molecules with tailored intermolecular interaction strengths and topologies to direct molecular self‐assembly as exemplified by the adsorption of 1‐adamantanethiol molecules on Au{111} substrates. 1‐Adamantanethiolate self‐assembled monolayers exhibit decreased packing densities and weaker intermolecular interaction strengths than n‐alkanethiolate self‐assembled monolayers, which result in their complete displacement upon exposure to n‐alkanethiol molecules. Herein, we explore the capabilities of the atomic force microscopy‐based lithographic technique, nanografting, to fabricate chemical patterns comprised of 1‐adamantanethiolate monolayers. Positive 1‐adamantanethiolate patterns are generated by nanografting 1‐adamantanethiol molecules into preexisting n‐alkanethiolate self‐assembled monolayers, and negative 1‐adamantanethiolate patterns are created by nanografting n‐alkanethiol molecules into preexisting 1‐adamantanethiolate self‐assembled monolayers. The patterned 1‐adamantanethiolate regions are displaced upon exposure to solutions of n‐alkanethiol molecules. This two‐step nanografting‐displacement strategy minimizes pattern dissolution as 1‐adamantanethiol molecules do not intercalate into the preexisting self‐assembled monolayer during nanografting. 1‐Adamantanethiol can be utilized create high‐resolution sacrificial chemical patterns with feature sizes beyond those afforded other 1‐adamantanethiol patterning strategies for applications such as resists for metallic and organic structures. SCANNING 37:6–16, 2015. © 2014 Wiley Periodicals, Inc.